Outsourcing motives, competitiveness and taxation - Jan König (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2010)
This paper shows the strategic aspects of international outsourcing in an oligopolistic market, if outsourcing is attractive because of fixed cost savings. We show that outsourcing decisions are strategic substitutes. Furthermore, we demonstrate that due to decreasing individual output, intensified competition increases the incentive to save fixed costs of integrated production and thus leads to more outsourcing. Additionally, we analyse how domestic costs and taxation affect the equilibrium level of outsourcing and employment. Here, we find that lower domestic costs decrease the proportion of outsourcing and therefore, increase employment. Concerning the impact of taxation, we find that a lower consumption tax on output decreases outsourcing. In case of a reversed outsourcing motivation, where outsourcing is associated with lower marginal costs but higher fixed costs than the domestic production, we show that the opposite effects concerning competition and taxation occur.
Keywords: D20; L13; L22; L23; L24; 330; outsourcing; cost structure; Cournot-competition; taxation; Outsourcing; International; Kostenstruktur; Steuer; Internationaler Wettbewerb; Beschäftigungseffekt; Theorie